Identidades, tradições e resistências: um estudo sociológico da festa da rapadura no sertão de Pernambuco - Sá, Andréa Carla de Magalhães Campos (2020)
The “northeastern capital of rapadura” or the “sweetest city in the backlands of Pernambuco” or even the “land of the biggest rapadura in the world” are symbolic constructions with the power to forge notions of identity, tradition and cultural resistance around the same event: The Rapadura Festival (or Rapadura Fair), which takes place in Santa Cruz da Baixa Verde, a municipality of 13,000 inhabitants located in the Sertão de Pernambuco, more than 400 km from Recife. It is around this event that it was possible to investigate a complex relationship of forces between individuals and groups with different views of the world. It was possible to understand, based on the analysis of a popular celebration, struggles for social differentiation and specific sociability from a banal food at the northeastern table. The present research sought to evidence multiple meanings that an apparently unpretentious party carries as a sociological phenomenon. With that, it was discovered how the appropriation of rapadura in Santa Cruz carries with it a conflicting range of values and interests that can culminate in the preservation of a way of making food or in the total destruction of popular knowledge that has existed for centuries.